1998
DOI: 10.1093/ajcn/68.2.266
|View full text |Cite
|
Sign up to set email alerts
|

Under- and overreporting of energy intake related to weight status and lifestyle in a nationwide sample

Abstract: Desire for weight change and level of dietary consciousness may severely bias reported food intake in dietary surveys. We evaluated to what degree under- and overreporting of energy intake (EI) was related to lifestyle, sociodemographic variables, and attitudes about body weight and diet in a nationwide dietary survey. Data were gathered by a self-administered quantitative food-frequency questionnaire distributed to a representative sample of men and women aged 16-79 y in Norway, of whom 3144 subjects (63%) re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

50
356
22
13

Year Published

2001
2001
2010
2010

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 416 publications
(441 citation statements)
references
References 14 publications
50
356
22
13
Order By: Relevance
“…Earlier studies of under-and over-reporters have mainly investigated either very wide age spans or younger ages. The prevalence of underreporters in the present population was 10 % compared with 16 % seen in a group of 16-19-year-olds in a Norwegian study (9) . In the same age group in the Norwegian study, 23 % were classed as over-reporters v. 22 % in the present study.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…Earlier studies of under-and over-reporters have mainly investigated either very wide age spans or younger ages. The prevalence of underreporters in the present population was 10 % compared with 16 % seen in a group of 16-19-year-olds in a Norwegian study (9) . In the same age group in the Norwegian study, 23 % were classed as over-reporters v. 22 % in the present study.…”
Section: Discussioncontrasting
confidence: 61%
“…In a review, Black et al (1) concluded that underreporting and under-eating occur in most dietary assessments, but with varying frequency according to the dietary assessment method used. Several characteristics of under-reporters, such as high BMI, high body fat percentage, food-specific reporting, low intake of fat, and high intake of protein and micronutrients, have been presented (4)(5)(6)(7)(8)(9)(10)(11)(12)(13) .Only a few studies have investigated the frequency and characteristics of over-reporting. Young, lean males have been found to be a group with a relatively high prevalence of over-reporting (9,12) , but data are sparse.…”
mentioning
confidence: 99%
“…First, the surveys relied entirely on self-report, which may have led to underestimates of weight and BMI, 22 as well as biased reports of the behavioural characteristics assessed. For example, obese respondents may be more likely to underreport energy intake than those of healthy weight, 44 an effect that, if present in this study, may explain the lack of any difference in consumption of fast foods and ED snacks between weight status groups. Objective measures of adiposity, and also of dietary intake, physical activity and sedentary behaviour, may result in stronger associations between these variables than observed here.…”
Section: Discussionmentioning
confidence: 74%
“…(Table 3). Several previous studies have already examined non-dietary factors, such as physiological (Zhang et al, 2000;Livingstone and Black, 2003) and psychological (Johansson et al, 1998;Bathalon et al, 2000;Tooze et al, 2004) factors associated with reporting accuracy of energy intake. After adjusting for these variables, the validity slightly improved (Pearson correlation coefficient was 0.42 for men and 0.37 for women).…”
Section: Discussionmentioning
confidence: 99%